A Personalized Food Recommendation Chatbot System for Diabetes Patients - Thongyoo, Phupat; Anantapanya, Phuttipong; Jamsri, Pornsuree; Chotipant, Supannada (My University, 2020)
Diabetes is a disorder of the body that is unable to produce enough insulin. Diabetes causes the body to improperly burn sugar, which affects the blood sugar level leaving a sugar residue. Diabetes is related to genes, body weight, lack of exercise and aging. When patients with diabetes neglect good nutrition this can cause many health problems. This research, therefore, develops a chatbot named “Waan-Noy” to recommend a diet suitable for individuals with diabetes and build a cooperative health society. Our chatbot recommends personalized eating. It is suitable for use by diabetes patients as indicated by their evaluations. Through use of nutrition therapy controls, Waan-Noy recommends specific foods. The user’s evaluation is divided into 3 areas: content, design, and implementation to determine user degree of satisfaction with Waan-Noy.
Keywords: Cooperative health society; Diabetes; Food recommendation; Health chatbot; Nutrition therapy